Kebutuhan Ruang dan Pola Tata Letak Parkir pada Area Sekolah Dasar Islam Terpadu (SDIT) Rahmaniyah Depok Jawa Barat - Artiwi, Nila Prasetyo (BENTANG : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2019)
Islamic Elementary School (SDIT) Rahmaniyah Depok, West Java, has 1059 students and 140 staffs (academic year of 2015/2016). Parking activity at school in the morning (students arrival) and in the afternoon and evening (students leave the school) is quite high. The current parking area is 1.260 m2.. It can handle 54 Parking Unit Area. Based on the surveys (five working days), delay and queue always happen to the shuttle cars at school during dropping and picking up the students. Therefore, the parking activity is on street parking. This situation makes chaos and inconvenience as well as high risk of accidents for students who are walking across or walking around in the school. After surveying, collecting, and calculating data, it can be concluded that the parking area that are provided hasn’t fulfilled the needs of parking area for the whole shuttle cars. Results showed the maximum parking accumulation reaches 110 cars, with the maximum parking volume of 657 cars, and the duration parking that reach the maximum amount of cars is 30 minutes. The study showed the school needs 1.820m2 parking area with the capacity of 82 Parking Unit Area. In the future, the school may need to arrange a plan to provide vertical parking space or with hydraulic system.